COMPARATIVE STUDY OF NEBIVOLOL VERSUS ATENOLOL IN THE TREATMENT OF MILD AND MODERATE ESSENTIAL HYPERTENSION. - V. SUSMITHA; Ch.V.NAGANJANI (International Journal of Pharma and Bio Sciences, 2013)
Nebivolol, β1 selective drug is a third generation β blocker with nitric oxide donating antiproliferative and antioxidant properties which are useful to maintain a proper metabolic profile compared to atenolol, a β1 selective drug most commonly used. A prospective randomized parallel double blind study was conducted in patients with essential hypertension. Group A received nebivolol and group B received atenolol for 12 weeks. Baseline investigations were carried out before and after the study. The data was statistically analysed using students ‘T’ test. Both atenolol and nebovolol showed significant reduction in both systolic blood pressure and diastolic blood pressure (P<0.001) after 12 weeks. Heart rate was significantly reduced (P<0.001) in the group that received atenolol. Blood sugar was significantly increased (P<0.001) in atenolol group after 12 weeks. It was concluded that nebivolol was better than atenolol in terms of improvement in blood sugar and heart rate.